Carry on, warrior [compact disc, unabridged] : thoughts on life unarmed - Doyle, Glennon, 1976- (Simon & Schuster Audio, 2013)
Melton shares her journey from reckless college girl hooked on alcohol, drugs, bulimia, and toxic relationships to becoming a sober and devoted wife, mother, daughter, sister and teacher. Her stories embody her need to tell and hear the truth, to be sometimes brave and sometimes silent, to say I'm sorry, to trust in something more powerful than herself, and to stop making motherhood, marriage, and friendship harder by pretending they're not hard.